2003
DOI: 10.1073/pnas.2131686100
|View full text |Cite
|
Sign up to set email alerts
|

A genetic lesion that arrests plasma cell homing to the bone marrow

Abstract: The coordinated regulation of chemokine responsiveness plays a critical role in the development of humoral immunity. After antigen challenge and B cell activation, the emerging plasma cells (PCs) undergo CXCL12-induced chemotaxis to the bone marrow, where they produce Ab and persist. Here we show that PCs, but not B cells or T cells from lupus-prone NZM mice, are deficient in CXCL12-induced migration. PC unresponsiveness to CXCL12 results in a marked accumulation of PCs in the spleen of mice, and a concordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 58 publications
4
58
1
Order By: Relevance
“…In addition, we have previously shown that both NZM2410 and NZW mice present an accumulation of PC in the spleen. 24 Although we were not able to map the entire phenotype to any single Sle locus, it is also temping to speculate that reduced FcgRIIB expression may contribute to this phenotype, as suggested by our data in Figure 6. Interestingly, close examination of our results in Figures 5 and 6 suggests that Sle1a also impacts the immune response to SRBC immunization, including the number of class-switched PCs.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, we have previously shown that both NZM2410 and NZW mice present an accumulation of PC in the spleen. 24 Although we were not able to map the entire phenotype to any single Sle locus, it is also temping to speculate that reduced FcgRIIB expression may contribute to this phenotype, as suggested by our data in Figure 6. Interestingly, close examination of our results in Figures 5 and 6 suggests that Sle1a also impacts the immune response to SRBC immunization, including the number of class-switched PCs.…”
Section: Resultsmentioning
confidence: 83%
“…28 Enzyme-linked immunospot (ELISPOT) assay AFCs were enumerated by ELISPOT as previously described. 24 Serially diluted RBC-depleted spleen and BM cells were added to multiscreen filter plates (Millipore, MA, USA) coated with 5 mg/ml goat antimouse IgG for 6 h at 37 1C. Bound cells were detected with HRP-conjugated-anti-IgG (Southern Biotechnology), and developed by 3-amino-9-ethylcarbazole (AEC, Sigma-Aldrich, St Louis, MO, USA).…”
Section: Immunohistologymentioning
confidence: 99%
“…Studies are underway to determine whether autoantibodies that arise naturally in autoimmune settings are derived from long-lived or short-lived AFCs. In the New Zealand Black/White and New Zealand M2410 models, the presence of long-lived AFCs has been documented, and interestingly, they have been shown to reside at unique sites (83)(84)(85). Clearly, more studies are warranted to better understand what governs B cell fate decisions in healthy vs autoimmune settings, the outcome of which may have important implications for B cell depletion strategies currently used to treat human autoimmune diseases (86,87).…”
Section: Discussionmentioning
confidence: 99%
“…GPI-specific IgG1-secreting cells in the spleen, LNs, and bone marrow (BM) were enumerated by GPI-specific ELISPOT assays as previously described, with modifications (22). In brief, 96-well multiscreen plates (Millipore) were coated with rabbit GPI (Sigma-Aldrich) and blocked with RPMI 1640 medium containing 10% FBS.…”
Section: Elisa and Elispot Assaysmentioning
confidence: 99%